2008
DOI: 10.1029/2008gl033462
|View full text |Cite
|
Sign up to set email alerts
|

Marine aerosol chemistry gradients: Elucidating primary and secondary processes and fluxes

Abstract: [1] Production mechanisms of aerosol chemical species, in terms of primary and secondary processes, were studied using vertical concentration gradient measurements at the coastal research station in Mace Head, Ireland. Total gravimetric PM1.0 mass, sea salt and water insoluble organic carbon (WIOC) concentration profiles showed a net production at the surface (i.e. primary production), while nssSO 4 and water soluble organic carbon (WSOC) concentration profiles showed a net removal at the surface. These observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 14 publications
10
93
1
Order By: Relevance
“…SC and CR activation curves converge at high s, likely because the WSOC concentration is high enough to notably decrease surface depression, more for organics in SC than for CR (Figure 3). The difference in CCN activity is consistent with studies to date (e.g., [16,56]), showing that hygroscopic components tend to be incorporated in cloud droplets where their less hygroscopic counterparts prefer to remain in the interstitial air. It is also noted that the CR samples excluded droplets <5 μm diameter thus the excluded smaller droplets may potentially contain less hygroscopic materials.…”
Section: Surface Tensionsupporting
confidence: 79%
See 2 more Smart Citations
“…SC and CR activation curves converge at high s, likely because the WSOC concentration is high enough to notably decrease surface depression, more for organics in SC than for CR (Figure 3). The difference in CCN activity is consistent with studies to date (e.g., [16,56]), showing that hygroscopic components tend to be incorporated in cloud droplets where their less hygroscopic counterparts prefer to remain in the interstitial air. It is also noted that the CR samples excluded droplets <5 μm diameter thus the excluded smaller droplets may potentially contain less hygroscopic materials.…”
Section: Surface Tensionsupporting
confidence: 79%
“…; Table 4), possibly long-chained aliphatic compounds within primary organic matter transferred to the aerosol from bubble bursting at the seawater surface [16,34,54,59,60]. The marine nature of the SC sample is further supported by its inferred surface tension depression (Figure 3, which is remarkably consistent with dissolved organic matter [34].…”
Section: Inferred Molar Volumes and Uncertaintiessupporting
confidence: 64%
See 1 more Smart Citation
“…The same authors also reported the results of principal component analysis, eddy-correlation flux measurements and Aerosol Mass Spectrometry gradient measurements, confirming a very low contribution of the shoreline to aerosol number concentration at Mace Head. In a subsequent experiment, Ceburnis et al (2008) estimated that coastal-generated aerosol might contribute between 5-20% of the aerosol particle mass concentration at Mace Head in the 3-30 m surface layer, but argued that the effect on chemical composition and subsequent chemical fluxes was not significant.…”
Section: Introductionmentioning
confidence: 99%
“…This result may suggest a minor contribution of water-soluble organic matter in summer due to a negligible contribution of aged continental air masses and/or significant contribution from marine biota. Based on the gradient flux measurements, Ceburnis et al (2008) found that water-insoluble organic matter (WIOM) exhibited an upward flux, whereas water-soluble organic matter (WSOM) exhibited a downward flux, suggesting a primary production for WIOM and a secondary formation for WSOM. In this study, WIOM/WSOM ratios were higher in summer (mean: 1.45 ± 0.17) and autumn (0.35 ± 0.57) than in winter (0.19 ± 0.67) as shown in Fig.…”
Section: Monthly/seasonal Variationsmentioning
confidence: 99%